Peningkatan Kualitas Produk Benang dengan Pendekatan Six Sigma - Sugeng Purwoko (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
Six Sigma had developed by Motorola in 1980 which was a system that more comprehensive and flexible to achieve succeful business. Eratex Djaja company is a company briefly making clothes that operates its business still has contrains and needed well handling. The implementation of six sigma method in repairing process is extremely needed to increase the company operational. Analysis and repairing alternatives are developed from recommended action FMEA and implemented by suitability of company condition. The objective of the research was to reduce defect waste that found more than 3,4 DPMO (Defect Permillion Opptunities) to achieve satisfied customer, also repairing and continuosly increasing quality from the company is based on specification and necessity of customers. The steps of this research were difine to identify a problem, measure to determine the problem influencetial in it then done measuring the DPMO (Defect Permillion Opptunities), analyze has contents of fish bone diagram to assist finding main problems that cause defect waste and improve is about FMEA (Failure Mode and Effect Analysis) to help in determining the alternative solution repairing that are given. One serious kind of defective to the quality is defect waste. Defect waste is defective to the yarn which fibrous part of yarns are trash, it has been in cone winding process. To reduce the defect waste is given by checking the worn-out component and giving lubncat to machine regularly.